ADAPTIVE STRATEGY IN BUILDING COMPETITIVE ADVANTAGE OF MSMES: INTEGRATION OF INNOVATION, DIGITALIZATION, AND SUSTAINABILITY - Agus F Abdillah; R. Nur Ali Yahya; Arya Fajar; Surya Dzaka Prayoga; Rizqa Maula Azzahra; Frisya Elflaritavadea; Vika Nurdiyana; Rafli Anggit Maolana; Jihan Nabilla Agustina; Amanda Maylasari Aysiva; Firsya Alflaretavadea (RADJA PUBLIKA, 2026)
This study analyzes the integration of product innovation, digitalization, and sustainability in shaping the competitive advantage of MSMEs in Gunung Pati. The research responds to a gap in the literature, which still examines these three variables separately and assumes that strategy is planned, whereas MSME practices demonstrate adaptive and contextual patterns. This study employs a qualitative approach with a multiple case study design, using observation, in-depth interviews, and documentation as data collection techniques. Data were analyzed using thematic analysis and cross-case analysis. The findings reveal that competitive advantage is formed through the integration of the three variables, which develop organically. Innovation is contextual and based on local creativity, digitalization is utilized adaptively but not yet strategically, and sustainability functions more as operational efficiency rather than formal differentiation. This integration is not planned but emerges as an adaptive and context-based emergent strategy. This study contributes by extending the Resource-Based View and dynamic capabilities perspectives through a contextual approach and provides practical implications for developing adaptive and sustainable MSME strategies.